SYMBOLIC MEANING OF BASAHA ISIFU RITUALS: THE TRADITION OF MUNA SOCIETY PRIOR TO NISFU SYA'BAN NIGHT IN MUNA REGENCY - Rahmat Sewa Suraya; Wa Ode Siti Hafsah; La Niampe; Heniman Heniman (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
During Nisfu shay'ban night in Muna community, various good practices are performed. These practices aim to achieve the primacy of the Nisfushay'ban night which usually starts after the evening prayer by reciting Yasin for three times and ends it with prayer. To welcome the night of Nisfu shay'ban, Muna community performed a ritual called “the Basaha Isifu”. The purposes of this study are (1) to find out the process of conducting the Basaha Isifu tradition in the community of KosundanoSub-district, (2) to understand the symbolic meanings of Basaha Isifu tradition. The location of this research was in Kosundano Subdistrict of Muna community. The data was collected through observation, interviews and documentation. The informants were selected using purposive sampling technique. The data analysis employed a qualitative descriptive analysis which includes data reduction, display data, and conclusion. The results of this study indicates that the implementation of Basaha Isifu tradition starts from (1) the preparation of all stuff needed for the ritual, (2) the implementation indicated by the prayer recitation, and (3) the closure indicated by the attendants shaking hands and enjoying dishes together. Symbolically, Basaha Isifu carried out by Muna community can be interpreted as a form of gratitude for the blessing of Allah SWT for wealth, longevity, health, and safety of all dangers